Noble Metal-Free Hierarchical ZrY Zeolite Efficient for Hydrogenation of Biomass-Derived Levulinic Acid - Hu, Di; Xu, Hong; Wu, Zuotong; Zhang, Man; Zhao, Zhiyue; Wang, Yuchen; Yan, Kai (Frontiers in Chemistry, 2021)
Developing a low-cost and robust catalyst for efficient transformation of biomass-derived platform chemicals plays a crucial role in the synthesis of future transportation fuels. Herein, a post-synthetic strategy was employed to develop a noble metal-free and robust ZrY zeolite catalyst, which is efficient for the hydrogenation of biomass-derived levulinic acid (LA) into biofuel γ-valerolactone (GVL), whereas over 95% yield of GVL was achieved in 10 h at 220°C. The effects of acidic properties from ZrY catalysts and various reaction parameters on the catalytic performance were then discussed in detail. Subsequently, different characterization tools were used to compare the difference and relationship of structure activity between the fresh and spent ZrY catalysts. It was found that acidity and the metal–support interaction were important for the direct synthesis of GVL. This work provides a guideline to design a noble metal-free catalyst for high-value utilization of biomass-derived sources.